2019
DOI: 10.1111/jfpp.14114
|View full text |Cite
|
Sign up to set email alerts
|

Development of cellulose nanofibers coating incorporated with ginger essential oil and citric acid to extend the shelf life of ready‐to‐cook barbecue chicken

Abstract: This study was aimed to assess the impact of cellulose nanofibers (CNF) edible coating incorporated with ginger essential oil (GEO) and citric acid (CA) on the shelf life of the ready‐to‐cook barbecue chicken meat. The treatments containing ginger essential oil and citric acid significantly reduced the microbial population compared with the control and cellulose nanofibers. The most effective treatment was the CNF + GEO 2% + CA 1%, which increased the meat shelf life up to 6 days. The highest chemical changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…The flavor of ginger makes it an excellent condiment and appetizer that is popular in food items. Khaledian et al evaluated the effects of electrospinning of cellulose nanofiber (CNF) integrated with ginger essential oil (GEO) and citric acid (CA) on the chemical, microbial, and sensory characteristics of barbecued chicken meat [ 251 ]. Microbial analysis observed that CNF-GEO-CA showed the highest activity against the main microbes involved in chicken-meat spoilage, such as Enterobacteriaceae species, Pseudomonas species, total aerobic psychotropic bacteria, lactic acid bacteria, and fungi (yeasts and molds) compared to control and CNF treatments [ 239 , 252 , 253 , 254 ].…”
Section: The Rationale Of Encapsulation Of Essential Oils Into Polymeric Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…The flavor of ginger makes it an excellent condiment and appetizer that is popular in food items. Khaledian et al evaluated the effects of electrospinning of cellulose nanofiber (CNF) integrated with ginger essential oil (GEO) and citric acid (CA) on the chemical, microbial, and sensory characteristics of barbecued chicken meat [ 251 ]. Microbial analysis observed that CNF-GEO-CA showed the highest activity against the main microbes involved in chicken-meat spoilage, such as Enterobacteriaceae species, Pseudomonas species, total aerobic psychotropic bacteria, lactic acid bacteria, and fungi (yeasts and molds) compared to control and CNF treatments [ 239 , 252 , 253 , 254 ].…”
Section: The Rationale Of Encapsulation Of Essential Oils Into Polymeric Nanofibersmentioning
confidence: 99%
“…Silva et al fabricated ultrafine fibers by incorporating ginger essential oil (GEO) into zein (Z); polyethylene oxide (PEO), and soy protein isolate (SPI) polymers via electrospinning to restrain Listeria monocytogenes growth in fresh Mina’s cheese [ 251 ]. The GEO showed antibacterial activity against Escherichia coli 0157:H7, Listeria monocytogenes , Salmonella typhimurium , Staphylococcus aureus, and Pseudomonas aeruginosa.…”
Section: The Rationale Of Encapsulation Of Essential Oils Into Polymeric Nanofibersmentioning
confidence: 99%
“…Maillard compounds (hundreds of them) results from a sequence of non-enzymatic reactions (Figure 9), which start from sugars and an amino group (typically from an amino acid or protein) through room temperature to approximately 200 • C. These compounds are very good antioxidants, but they are usually associated with cooking processes (some of them) such as the flavors, aroma, and brown color released by baked food. Essential oil contains mainly terpenic compounds that are responsible for the antibacterial and antioxidant properties of films: monoterpenes (limonene, tricyclene, α-thujene, α-pinene, camphene, sabinene, β-pinene, β-myrcene, 3-carene, α-terpinene, α-phellandrene, p-cymene, υ-terpinene, α-terpinolene), oxigenated monoterpene (1,8-cineole (Z)-sabinenehydrate, linalool, d-fenchylalcohol, α-campholenal, camphor, borneol, 4-terpineol, α-terpineol, bornylacetate), sesquiterpene hydrocarbon (α-copaene, aromadendrene α, (E)-caryophyllene, alpha-amorphene, 7-cadinene, δ-cadinene), oxygenated sesquiterpene (caryophyllene oxide, α-eudesmol) [12,[117][118][119][120][121][122][123][124][125][126]. These molecules comply with the Code of Federal Regulations; they are GRAS, GRAS/FS, GMP, and are very effective, but their use is subject to controversy in the food industry, and replacements are needed (except for the natural product, and even for them, the use is allowed only after a careful evaluation of effects).…”
Section: Additivesmentioning
confidence: 99%
“…Total phenolic contents (TPC) (Folin-Ciocalteu reagent) data are expressed in equivalents of mg of gallic acid for 100 g of film (mg GAE/100 g film) [78,[118][119][120]155,156,[215][216][217][218][219][220][221][222][223][224][225][226][227][228].…”
Section: Antioxidant and Antimicrobial Activitymentioning
confidence: 99%
“…The herbal EOs may therefore not affect the microorganisms that are in the aqueous phase of the food because of their oily nature 9 . Moreover, the minimum concentrations needed for the antimicrobial effects of the EOs are higher in food than the culture medium, which may cause unpleasant changes in the food's taste and smell 10 …”
Section: Introductionmentioning
confidence: 99%